Kisah Nabi Musa dalam al-Qur’ān Perspektif Psiko-Sastra - Ahmad Ashabul Kahfi (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
The story of Moses dominates most the whole story in the Quran. When one assumes that the Qur’ān belongs to the Prophet Moses, it is then a fairly common assumption. The narrative method is one of the best methods to convey messages and lessons, especially religious messages. It has been a reason why the Qur’ān covers more narrative verses than laws and commands. This article deals with a new approach in understanding such narration, which so-called literary psychology. This approach has been used to understanding personality of the individual mentioned in the story. Such personality is regarded as an important lesson to inspire and motivate the readers. The psychological theory commonly used in this approach is the religious coping strategy. This approach draws a conclusion which shows that Moses possessed a virtuous religious coping strategy. This approach can be a way out to solve the old method of interpretation of the story that unable to address the psychological aspects of the Prophet Moses as well as to develop the integration-interconnection paradigm of Islamic scholars with general science.